Pengaruh Mediasi Ekuitas Merek Terhadap Keputusan Pembelian IPhone Konsumen di Jakarta, Indonesia - Shabrina Zata Amani (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2022)
This study examines the factors that determine brand equity and its influence on consumer iPhone purchasing decisions. It focuses on the Mediation Effect of Brand Equity on Consumer Purchase Decisions in Jakarta, Indonesia. The questionnaire survey method was used in primary data collection by distributing google forms through social media. Sampling is non-probability with a conventional method. And the sampling technique with the minimum sample size determinant for SEM (Structural Equation Model) according to Hair et al (2010) determination of the sample with a count (Number of indicators + the number of variables) x (5 to 10 times). Following these guidelines, the study requires a minimum sample size of 175 respondents. In this study the researchers got as many as 202 respondents. In assessing the views of consumers' purchasing decisions, it was found that brand loyalty, brand awareness, perceived quality, and brand associations significantly influenced consumers' purchasing decisions. Among these, brand loyalty appears to be the strongest factor and has a significant positive path. This shows that higher brand loyalty leads to higher consumer purchasing decisions. Other significant variables also have a positive relationship. Then from this study also shows that there is an influence of brand loyalty variables, brand awareness, perceived quality, and brand associations on consumer purchasing decisions through brand equity mediation.